Aplicação de regulador vegetal e poda nas relações fisiológicas na produção do tomateiro - Spadoni, Thais Botamede [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Two experiments were conducted, the first with the aim to evaluate the best stage for performing foliar application of the mixture of auxin (Ax), cytokinins (CK) and gibberellins (GA), in particular tomato (Solanum lycopersicum L.), using a dose of 0,20% of the product. The second experiment in order to evaluate the effect of Belgian pruning and the influence of mixing auxin (Ax), cytokinin (CK) and gibberellic acid (GA) in the development and metabolism of plants. The first experiment was conducted in the experimental area of the Faculty of Agricultural Sciences at the Universidade Estadual Paulista-UNESP, in São Manuel. The experimental design was randomized blocks with 16 treatments, four replications: T1:Control; T2: Before Transplant; T3: Before Transplant + Rooting; T4: Before Transplant + Rooting + Sprouting; T5: Before Transplant + Rooting + Sprouting + Starts Flowering; T6: Before Transplant + Rooting + Sprouting + Starts Flowering+ Starts Fruiting; T7: Rooting; T8: Rooting + Sprouting; T9: Rooting + Sprouting + Ínicio do Florescimento; T10: Rooting + Sprouting + Starts Flowering+ Starts Fruiting; T11: Sprouting (mesmo dia); T12: Sprouting + Starts Flowering; T13: Sprouting + Starts Flowering+ Starts Fruiting; T14: Starts Flowering; T15: Starts Flowering+ Starts Fruiting; T16: Starts Fruiting. The second experiment was conducted ...

Realizou-se dois experimentos, sendo o primeiro com objetivo em avaliar o melhor estádio para se realizar a aplicação foliar da mistura de auxina (Ax), citocinina (CK) e giberelina (GA), em tomate determinado (Solanum lycopersicum L.), utilizando-se a dose de 0,20% do produto. O segundo experimento com objetivo em avaliar o efeito da poda belga e a influência da mistura de auxina (Ax), citocinina (CK) e giberelina (GA) no desenvolvimento e metabolismos das plantas. O primeiro experimento foi conduzido na área experimental da Faculdade de Ciências Agronômicas da Universidade Estadual Paulista-UNESP, em São Manuel. Foi utilizado delineamento de blocos ao acaso sendo 16 tratamentos, quatro repetições: T1: Testemunha; T2: Antes do transplante; T3: Antes do transplante + Enraizamento; T4: Antes do transplante + Enraizamento + Desbrota; T5: Antes do transplante + Enraizamento + Desbrota + Início do Florescimento; T6: Antes do transplante + Enraizamento + Desbrota + Início do Florescimento+ Frutificação; T7: Enraizamento; T8: Enraizamento + Desbrota; T9: Enraizamento + Desbrota + Ínicio do Florescimento; T10: Enraizamento + Desbrota + Início do Florescimento+ Frutificação; T11: Desbrota (mesmo dia); T12: Desbrota ...
Plant regulator application and pruning on physiological relations in tomato production
Keywords: Tomate - Poda; Plantas - Metabolismo; Hormonios vegetais; Plantas - Transpiração; Tomatoes